Rhizosphere Engineering With Plant Growth-Promoting Microorganisms for Agriculture and Ecological Sustainability - Hakim, Sughra; Naqqash, Tahir; Nawaz, Muhammad Shoib; Laraib, Iqra; Siddique, Muhammad Jawad; Zia, Rabisa; Mirza, Muhammad Sajjad; Imran, Asma (Frontiers in Sustainable Food Systems, 2021)
The rhizosphere is undoubtedly the most complex microhabitat, comprised of an integrated network of plant roots, soil, and a diverse consortium of bacteria, fungi, eukaryotes, and archaea. The rhizosphere conditions have a direct impact on crop growth and yield. Nutrient-rich rhizosphere environments stimulate plant growth and yield and vice versa. Extensive cultivation exhaust most of the soils which needs to be nurtured before or during next crop. Chemical fertilizers are the major source of crop nutrients but their uncontrolled and widespread usage has posed a serious threat to sustainability of agriculture and stability of ecosystem. These chemicals are accumulated in soil, drained in water, and emitted to the air where they persist for decades causing serious threat to overall ecosystem. Plant growth promoting rhizobacteria (PGPR) present in the rhizosphere convert many plant-unavailable essential nutrients e.g., nitrogen, phosphorous, zinc etc. into available forms. PGPR produce certain plant growth hormones (such as auxin, cytokinin, and gibberellin), cell lytic enzymes (chitinase, protease, hydrolases etc.), secondary metabolites and antibiotics, and stress alleviating compounds (e.g., 1-Aminocyclopropane-1- carboxylate deaminase), chelating agents (siderophores). They different signaling compouds (e.g., N-Acyl homoserine lactones to interaction with the beneficial or pathogenic counterparts in the rhizosphere. These multifarious activities of PGPR improve the soil structure, health, fertility and functioning which directly or indirectly support plant growth under normal and stressed environments. Rhizosphere engineering with these PGPR has a wide ranging application not only for crop fertilization but developing eco-friendly sustainable agriculture. Due to severe climate change effects on plants and rhizosphere biology, there is growing interest in stress-resilient PGPM and their subsequent application to induce stress (drought, salinity, and heat) tolerance mechanism in plants. This review describes the three components of rhizosphere engineering with an explicit focus on the broader perspective of PGPM that could facilitate rhizosphere engineering in selected hosts to serve as an efficient component for sustainable agriculture.